Dechema corrosion handbook. - Kreysa, Gerhard; Schütze, Michael (Dechema, 2008)
Compendium of corrosion data describing the corrosion and chemical resistance of all technically important metallic, non-metallic, inorganic, and organic materials in contact with aggressive media.